Learning through evaluation – A tentative evaluative scheme for sustainability transition experiments. (15th December 2017) - Luederitz, Christopher; Schäpke, Niko; Wiek, Arnim; Lang, Daniel J.; Bergmann, Matthias; Bos, Joannette J.; Burch, Sarah; Davies, Anna; Evans, James; König, Ariane; Farrelly, Megan A.; Forrest, Nigel; et al.
Abstract: Transitions towards sustainability are urgently needed to address the interconnected challenges of economic development, ecological integrity, and social justice, from local to global scales. Around the world, collaborative science-society initiatives are forming to conduct experiments in support of sustainability transitions. Such experiments, if carefully designed, provide significant learning opportunities for making progress on transition efforts. Yet, there is no broadly applicable evaluative scheme available to capture this critical information across a large number of cases, and to guide the design of transition experiments. To address this gap, the article develops such a scheme, in a tentative form, drawing on evaluative research and sustainability transitions scholarship, alongside insights from empirical cases. We critically discuss the scheme's key features of being generic, comprehensive, operational, and formative. Furthermore, we invite scholars and practitioners to apply, reflect and further develop the proposed tentative scheme – making evaluation and experiments objects of learning. Highlights: A tentative scheme is presented to evaluate sustainability transition experiments. The scheme is applicable to different types of sustainability transition experiments. The scheme comprehensively captures the outcomes, inputs and mediating attributes. It is ready to be applied including guidance for specifying it to particular cases. It supports experiments in becoming more effective and efficient via reflection and learning.